Evaluating anesthesia practice for caesarean section: A prospective cross-sectional study from a tertiary care institution of low- and middle-income country - Samina Ismail; Malika Hameed (Wolters Kluwer Medknow Publications, 2021)
Background and Objective: In low and middle-income countries (LMICs), general anesthesia for cesarean section has shown to increase the odds of maternal mortality. Use of regional anesthesia for cesarean section is an indicator for safe practice of anesthesia; therefore, this study aims to evaluate the current practice of use of regional anesthesia and its failure rate for cesarean section. The current practice is analyzed in the light of previously published data from the same institution of LMIC. Methods: After hospital ethics committee approval, this prospective cross-sectional study was performed from January 1 to June 30, 2019. Prospective data collected on predesigned form included technique of anesthesia employed for different category of cesarean section, failure of regional anesthesia, and other related data. The cesarean section rate and trends of technique of anesthesia over last 10 years were collected from hospital record system. Results: Compared to the published data from the year 2012 from the same institution, the results from this prospective data have shown an increase rate of cesarean section rate from 31% to 52% with an overall decline in the use of general anesthesia from 49% to 12.3%. In addition, rate of regional anesthesia for category 1-3 cesarean section has increased from 46.4% to 79.8% and for category 1 from 37.1% to 63.4%. Decline in failure rate of regional technique was observed from 6.7% to 2.4%. Conclusion: Assessing and analyzing practices helps in taking initiative to implement safe practices which are needed to achieve the target for best practice.